An Experimental Investigation Of Perforated Manifolds To Enhance Stratification In A Solar Domestic Hot Water Tank (The International Journal of Engineering & Information Technology (IJEIT), 2021)
An experimental study was conducted to develop and test three perforated manifolds designed to enhance thermal stratification in a solar domestic hot water tank. The perforated manifolds extend from an immersion heat exchanger to the top of the tank. Experimental results were analyzed for each manifold to determine the most effective design. The thermal performance of the manifolds was evaluated in terms of the exergy and entropy of the water in the tank at the end of each test. It was found that perforated manifolds perform better than a conventional non-perforated manifold that delivers hot water to the top of the tank. Further work, especially using CFD tools, will help in identifying favorable perforated manifold designs.Solar domestic hot water tank